Atypical combinations of technologies in regional co-inventor networks - Milad Abbasiharofteh; Dieter F. Kogler; Balázs Lengyel (Research Policy, 2023)
Novel combinations of technologies are usually the result of collaborative work that builds on existing knowledge. Albeit inventors and their respective communities tend to be specialized, inventor collaborations across differently specialized peers have the potential to generate co-inventor networks that provide access to a diverse set of knowledge and facilitate the production of radical novelty. Previous research has demonstrated that short access in large co-inventor networks enables innovative outcomes in regional economies. However, how connections in the network across different technological knowledge domains matter and what impact they might generate is still unknown. The present investigation focuses on `atypical' combinations of technologies as indicated in patent documents. In particular, the role of technological specializations linked in co-inventor networks that result in radical innovation in European regions is analyzed. Our results confirm that the share of atypical patents is growing in regions where bridging ties establish short access to and across cohesive co-inventor sub-networks. Furthermore, the evidence suggests that the strong specialization of co-inventor communities in regions fosters atypical combinations because these communities manage to increase the scale and scope of novel combinations. Thus, bridges between communities that are specialized in different technologies favor atypical innovation outcomes. The work shows that not diversity per se, but links across variously specialized inventor communities can foster radical innovation.
Keywords: 330; invention; collaboration networks; small-world networks; network communities; technological similarity; network of places; patent analysis; regional economies